Tissue management in precision medicine: What the pathologist needs to know in the molecular era - Souza da Silva, Ricella; Pinto, Regina; Cirnes, Luis; Schmitt, Fernando (Frontiers in Molecular Biosciences, 2022)
The precision medicine is more than genomic medicine and represents the present/future of oncology. Pathology integrates multidisciplinary oncology teams of personalized medicine, however, although so familiarized with the cancer diagnosis and with tissue sample that is the beacon of druggable targets, still seems to need to adjust the understanding of its importance. In a broader and clearer understanding of that, precision medicine needs pathology to be precise. Pathologist involvement in genomic medicine and biomarkers starts with the management of tissue sampling. We present, in an objective and practical way, the pivotal and interconnected points related to pathology, which influence the success of molecular tests, seeking to address the steps related to the tissue sample management workflow: pre-analytical; diagnosis and select of correct material – peri-analytical morphomolecular; diagnosis and morphological control. The molecular tumor profiling and the comprehensive proteomic and genomic data in the context of morphology makes great strides. The way from pathology to precision oncology still has a good and long step to go: getting that the molecular test reaches to the clinical practice; keep learning in multidisciplinary committees for advancing disease and leaning for early disease.